Medieval perceptual puzzles : theories of sense perception in the 13th and 14th centuries - Băltuță, Elena (Investigating medieval philosophy, 2020)
"In our daily lives, we are surrounded by all sorts of things - such as trees, cars, persons, or madeleines - and perception allows us access to them. But what does 'to perceive' actually mean? What is it that we perceive? How do we perceive? Do we perceive the same way animals do? Does reason play a role in perception? Such questions occur naturally today. But was it the same in the past, centuries ago? The collected volume tackles this issue by turning to the Latin philosophy of the 13th and 14th centuries. Did medieval thinkers raise the same, or similar, questions as we do with respect to perception? What answers did they provide? What arguments did they make for raising the questions they did, and for the answers they gave to them? The philosophers taken into consideration are, among others, Albert the Great, Roger Bacon, William of Auvergne, Thomas Aquinas, Duns Scotus, John Pecham, Richard Rufus, Peter Olivi, Robert Kilwardby, John Buridan, and Jean of Jandun"--Back cover.